Rural development funding and wildfire prevention: Evidences of spatial mismatches with fire activity. (June 2022) - Colonico, Mario; Tomao, Antonio; Ascoli, Davide; Corona, Piermaria; Giannino, Francesco; Moris, Jose V.; Romano, Raoul; Salvati, Luca; Barbati, Anna
Abstract: The European Union Rural Development Program (RDP) is a major driver of landscape change over time in Europe. In a context of climate and land use changes and consequent fire risk exacerbation, understanding the possible contribution of RDP measures to wildfire risk mitigation could help planning subsidies allocation criteria in a more efficient way for fire prevention. However, little is known on the links between the spatial allocation of RDP subsidies, relevant for wildfires prevention, and the spatial distribution of fire activity. Our study aims to fill this knowledge gap through an exploratory analysis carried out in Italy and based on fire activity indicators of the period 2007–2017, RDP expenditure at municipal level in the period 2017–2013, and a series of ancillary indicators. We selected RDP measures specifically addressing wildfires (direct prevention) and those whose implementation has an impact on fire regime (indirect prevention). Our results suggest a low association between RDP expenditure for fire-related measures and subsequent reduction of wildfire activity. Principal Component Analysis suggests a role of managed rural areas in mitigating fire activity, as well as a spatial mismatch between wildfire prevention expenditure and high fire activity contexts. We claim the need for a deeper integration of territorial planning information within the RDP funding allocation criteria. Also, integrating RDP indirect prevention measures within fire management plans would be a cost-effective approach to leverage the impact of public policies on wildfire risk management, by allocating the limited financial resources to high-risk areas. Highlights: We selected RDP measures addressing both direct and indirect fire prevention. No significant correlation is found between expenditure on direct prevention and fire activity. A spatial mismatch between fire prevention measures and high fire activity contexts is found. A deeper integration of territorial planning information within the funding allocation criteria is needed. Indirect prevention measures would improve the impact of public policies on wildfire risk management.